IMPLEMENTASI PERATURAN KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 14 TAHUN 2014 TENTANG UNIT LAYANAN PENGADAAN BARANG/JASA PADA BIRO LOGISTIK POLDA MALUKU UTARA - Yusuf Praseteya; Nam Rumkel; Abdul Aziz Hakim (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
Regulation of the Chief National Police of the Republic of Indonesia Number 14 Year 2014 concerning Services Unit for Procurement of Goods/Services at the North Maluku Regional Police Logistics Bureau for the implementation of the procurement process for goods and services has been running in accordance with existing rules. But there are some things that have not been carried out based on the Regulation. With regard to consistency in the implementation of the rules, inconsistencies occur in the rules that have been set, because there are indeed some things that cannot be fulfilled by the organizational unit so that there are still mismatches between the realization and implementation of the rules themselves. Factors which become obstacles in the implementation of the Regulation of the Chief National Police of the Republic of Indonesia Number 14 Year 2014 include (1) Human Resources Factors; (2) Facilities and Infrastructure Factors; and (3) Rule/Legality Factors.